Digestibilidade aparente da quirera e farelo de arroz para o tambaqui (Colossoma macropomum, Cuvier, 1818) - Santana, Priscila Monise dos Santos (2017)
The apparent digestibility coefficients (ADC) of rice by - products (rice bran and broken rice) were estimated for the tambaqui Colossoma macropomum. Juveniles with a mean weight of 63.5 g (± 2.7) were distributed in conical bottom tanks with a capacity of 100 L. A reference diet was formulated according to the nutritional requirements of tambaqui, while two test diets consisted of 70% of the reference diet and 30% of rice bran or broken rice, with 0.5% of chromium oxide being incorporated as an external marker. CDA determination was performed by the Guelph method modified with excreta collection by sedimentation and quantification of chromium oxide. The dry matter (DM), crude protein (CP), ethereal (EE), crude fiber (FB) and crude energy (BW) of the reference diet were 71.7%, 88.9%, 86.1%, 42.6% and 91.6%, respectively. The dietary CDAs with rice bran were similar to those of the reference diet (MS, 72.6%, CP, 90.2%, EE, 86.0%, FB, 48.8%, and EB, 86.1% %). The diet with surgira presented CDAs of 74.3% for MS, 88.2% for PB; 82.8% for EE, 55.7% for FB and 84.1% for EB. Rice bran and broken rice were highly digested by tambaqui and could be used as ingredients in diets for this species.